STUDI LITERATUR KESULITAN DALAM PEGEMBANGAN BAHAN AJAR ARITMATIKA BERBASIS NILAI ISLAM BAGI CALON GURU - Yafnida, Neli; Nasywa Alya Syafitri; Kusno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics is often perceived as an abstract discipline detached from life values. However, in the perspective of Islamic education, knowledge should be integrated with spiritual and moral values. One form of such integration can be achieved through the development of mathematics teaching materials based on Islamic values. Nevertheless, the process of developing such materials faces various challenges, both conceptually, pedagogically, and technically. This study aims to identify and analyze the difficulties encountered in developing arithmetic teaching materials integrated with Islamic values for prospective teachers, as well as to examine the solutions proposed in previous research. The method employed is a systematic literature review, involving the collection, selection, analysis, and synthesis of relevant national and international studies. The results indicate that the difficulties in developing arithmetic teaching materials based on Islamic values can be categorized into three main aspects: conceptual, pedagogical, and technical-implementative difficulties. Conceptual difficulties arise from linking arithmetic concepts with Islamic values; pedagogical difficulties relate to the limited ability of prospective teachers to design contextual, value based learning; while technical and implementative difficulties concern limited resources, media, and assessment instruments. Several studies propose solutions such as integrative training for prospective teachers, the development of conceptual guidelines for integrating Islamic values into mathematical content, and the application of project-based and contextual learning approaches. Thus, this study provides a comprehensive overview of the challenges and future directions in developing Islamic value-based arithmetic teaching materials for prospective teachers.